Current Concepts in the Biopsy of Musculoskeletal Tumors: AAOS Exhibit Selection. (21st January 2015) - Traina, Francesco; Errani, Costantino; Toscano, Angelo; Pungetti, Camilla; Fabbri, Daniele; Mazzotti, Antonio; Donati, Davide; Faldini, Cesare
Abstract : Background: A musculoskeletal tumor biopsy can involve fine needle aspiration, core needle biopsy, or incisional biopsy. Controversy regarding the diagnostic yield of these biopsy techniques continues. The purpose of this article is to summarize the current concepts in the biopsy of musculoskeletal tumors. Methods: We performed a literature review of clinical articles reporting on the biopsy of bone and soft-tissue primary tumors. Clinical articles were excluded on the basis on abstract content if they represented case reports, review or opinion articles, or technique descriptions. Eighteen of the thirty-nine articles that remained were excluded because the results did not indicate the diagnostic accuracy of the various biopsy techniques. Thus, twenty-one articles with diagnostic data on the biopsy of bone and soft-tissue tumors were included in this review. Results: Core needle biopsy appeared to be more accurate than fine needle aspiration, and incisional biopsy appeared to be more accurate than both of these techniques, but the differences did not reach significance. Incisional biopsy was more expensive than the percutaneous biopsy methods. In deep musculoskeletal tumors, incorporation of ultrasonography or computed tomography for guidance is easy and safe and can be useful for increasing the accuracy of the biopsy. Advantages of a percutaneous technique compared with an incisional one are the low risk of contamination and the minimally invasive nature. Certain anatomic locations and histologic types were associated with diagnostic difficulty. Vertebral tumors had the lowest diagnostic accuracy regardless of the biopsy technique. Myxoid, infection, and round cell histologies were associated with the lowest diagnostic accuracy. Conclusions: The current literature has not clarified the optimal biopsy technique for the diagnosis of bone and soft-tissue tumors. However, core needle biopsy is usually preferable to incisional biopsy because of the low risk of contamination and the low cost. In addition, the use of imaging guidance increases the diagnostic accuracy of musculoskeletal biopsies and reduces the risk of complications. If the result of a percutaneous biopsy is nondiagnostic, a small incisional biopsy should be performed. Level of Evidence: DiagnosticLevel IV . See Instructions for Authors for a complete description of levels of evidence.